Avaliação da função visual de recém-nascidos prematuros - Bezerra, Ruth Batista (2021)
Introduction: In Brazil, despite the scarcity of population studies that demonstrate the prevalence and causes of visual impairment, important programs for visual screening in the pediatric population have been created with the aim of reducing the chances of developmental delay. Objectives: This study presents a protocol for the evaluation of different aspects of visual function of premature newborns still hospitalized and investigates the threshold of visual acuity of premature newborns. Material and Methods: This is a cross-sectional observational analytical study approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte under number 1.876.007, carried out in a public maternity hospital, located in the Northeast region of Brazil, reference in high-risk pregnancies in the state of Rio Grande do Norte. Data collection occurred during the period from February to October 2018 and the sample consisted of premature newborns admitted to the Neonatal Intensive Care Unit who had a corrected gestational age between 30 and 36 weeks and 6 days, which were clinically stable. The visual function was evaluated by 7 tasks compiled in a single Standard Operating Protocol and for the evaluation of Visual Acuity it was used in the Teller cards according to the manual's rules. During the study period, 59 newborns fulfilled the inclusion criteria and 42 were recovered, 17 were excluded for failing to reach the test due to a fall in alertness (drowsiness or crying). Results: Among the 7 aspects of the visual function taken, all were present in the neonatal period and the threshold of Visual Acuity of a premature newborn close to 32 weeks of corrected gestational age is 0.32 cpg.